Optimization handover procedure in IEEE 802.16E network - Misbah Emhammed, Misbah Abdelsalam; Ho, Yih Hwa (IJSER, 2014)
Mobile WiMAX is a broadband wireless access technology having the ability to carry voice, data and video services. When a mobile station shifts from one serving station to another, a handover operation takes place which has a critical effect on real-time applications. This study discusses some of the general aspects of handover in mobile WiMAX networks, the IEEE 802.16/WiMAX network architecture and the MAC layer features that enable handover mechanism. There is also an analysis of the effect of the packet size of generated packets per second and the effect of mobility with focus on the impact of packet size and mobile speed. Currently, the WiMAX standard asserted that hard handover is compulsory; therefore the focus of this study is hard handover while Macro diversity handover and fast base station switching are not the primary focus in this report.